Jógová terapie pro plochonoží - Kučerová, Ivana; Ivana Kučerová (České vysoké učení technické v Praze, 2021)
Předmětem bakalářské práce je výzkum využití jógových ásan při terapii plochonoží. V teoretické části jsou popsány nejdůležitější poznatky z anatomie a kineziologie nohy. Dále je zde zmíněna ontogeneze nohy a další její biomechanické vlastnosti – funkce kleneb chodidla a chůze. Následující část pojednává o klasifikaci a etiologii vzniku plochonoží a o různých možnostech terapie využívajících se ve fyzioterapii. V závěru teoretické části jsou popsány nejčastější vady spojené s touto problematikou. Metodologická část je věnována popisu použitých vyšetřovacích postupů. Je zde také podrobně popsána cvičební jednotka složená z jógových ásan, které byly použity k terapii. Ve speciální části je stanoven postup rehabilitace s využitím jógových ásan. Dále se věnuje zpracovaným vstupním vyšetřením jednotlivých probandů. V závěru práce je vyhodnocena úspěšnost této konzervativní terapie u plochonoží a průběh stanoveného rehabilitačního plánu. Získané výsledky jsou hodnoceny na základě porovnání vstupních a výstupních kineziologických rozborů, subjektivních pocitů probandů a pro objektivizaci výsledků jsou porovnány vstupní a výstupní otisky z baropodometrické plošiny FreeMed.

The subject of the bachelor thesis is the research of the use of yoga asanas as the therapy for flat feet. The theoretical part describes the most important findings from the anatomy and kinesiology of the foot. Furthermore, there is mentioned foot ontogenesis and its other biomechanical properties – the function of the foot arches and walk. The following part is about the classification and etiology of the formation of flat feet and about various treatment options used in physiotherapy. At the end of the theoretical part there are described the most common defects associated with this issue. The methodological part is dedicated to the description of used examination procedures. There is also a detailed description of the exercise unit composed of yoga asanas that have been used for the therapy. Special part is determined to the rehabilitation process with the use of yoga asanas. It also deals with the evaluated input examination of individual probands. At the end of the thesis there is evaluated the success of this conservative therapy for flat feet and the course of the established rehabilitation plan. The obtained results are evaluated on the basis of comparison of input and output kinesiological analyses and subjective feelings of proband. For the objectification of results there is also comparison of the input and output prints from the baropodometric platform FreeMed.
Yoga Therapy for Flat Feet
Keywords: Plochonoží; jóga; terapie; baropodometr; Flat feet; yoga; therapy; baropodometr